(untitled) (Eurasian Medical Research Periodical, 2023)
Diagnosis of chronic active hepatitis - study of liver function tests, serum markers of hepatitis viruses, immunological parameters, determination of antibodies to antigens, ultrasound and liver biopsy; rheumatoid arthritis - X-ray of the joints, a blood test for rheumatoid factor, for antibodies to citrullinated peptide and citrullinated vimentin; seronegative arthritis - X-ray of the joints of the lumbosacral spine, sacroiliac joints, a study for chlamydial infection, a blood test for rheumatoid factor. To diagnose tuberculosis of various localizations, x-rays and tomography of the lungs are performed, sputum and bronchial washings are examined, and a nephrourological examination with urinalysis, ultrasound is performed, X-ray methods are used (for tuberculosis of the kidneys and urinary system), an examination is prescribed by a urologist and gynecologist (for urogenital -tal tuberculosis).